Hamiltonian positivity of massive spin-2 particles via a rank-2 tensor - Benndorf, D. [UNESP]; Dalmazi, D. [UNESP]; Dos Santos, A. L.R. [UNESP] (IOP Publishing, 2017)
There are three families of Lagrangians describing massive spin-2 particles via a general (nonsymmetric) rank-2 tensor. Each of those families depends on an arbitrary real parameter, one of them includes the paradigmatic Fierz-Pauli theory whose Hamiltonian positivity is known and reviewed here. Here we apply the plain Dirac-Bergmann procedure in the two remaining families. We identify all Hamiltonian constraints and prove both positivity of the reduced Hamiltonian and correct counting of degrees of freedom. The positivity of each spin mode contribution is demonstrated by using spin projection operators. The massless cases are also examined. In particular, we prove positivity of the reduced Hamiltonian and correct counting of degrees of freedom of a Weyl invariant description of massless spin-2 particles.
Keywords: constraints; Fierz-Pauli; massive gravity; massive spin-2